Wavelength conversion in WDM networking. - Ramamurthy, B. (IEEE Journal on selected areas in communications)
Wavelength conversion has been proposed for use in wavelength-division multiplexed networks to improve efficiency. This study highlights systems challenges and performance issues which need to be addressed in order to incorporate wavelength conversion effectively. A review/survey of the enabling technologies, design methods, and analytical models used in wavelength-convertible networks is provided